Endoscopic mucosal resection of flat and sessile colorectal adenomas: Our experience with long-term follow-ups - Grgov, Saša; Dugalić, Predrag; Tomašević, Ratko; Tasić, Tomislav (Vojnosanitetski pregled, 2013)
Bacground/Aim. Endoscopic mucosal resection (EMR) or mucosectomy is a removing method of flat or sessile lesions, laterally spreading tumors and carcinoma of the colon or the rectum limited to mucosa or the surface part of the submucosa. The aim of the study was to estimate the efficacy and safety of EMR in removing flat and sessile colorectal adenomas. Methods. This prospective study involved 140 patients during the period of 8 years. A total of 187 colorectal adenomas were removed using the EMR method “inject and cut with snare”. Results. The approximate size of mucosectomised adenomas was 13.6 mm (from 8 mm to 60 mm). There was a total of 48 (25.7%) flat adenomas and 139 (74.3%) sessile adenomas, (p
Keywords: adenoma; colorectal neoplasms; endoscopy; digestive system; treatment outcome